Pengaruh Struktur Modal Dan Profitabilitas TerhadapNilai Perusahaan Dengan Kebijakan Deviden SebagaiVariabel Intervening(Studi pada Perusahaan Manufaktur yang terdaftar di BEI Tahun 2012-2014) - Septiani, Eka; , Drs. Atwal Arifin, Akt., M.Si (2017)
The purpose of this research is the influence of capital structure and profitability on the company with its dividend policy as variable intervening .Value of enterprise in this research is proxied by price book value ( PBV). Population in research it is a whole manufacturing companies who a listing on stock exchange indonesia of 2012-2014 .Samples to be taken with using a technique purposive sampling and the total samples from 40 companies for three years appropriate criteria .Technique analysis using test the assumption classical and analysis a track ( analysis path ) . Based on the research done in the analysis the is known to few things , as follows: ( 1 ) capital structure significant influence the dividend policy , ( 2 ) profitability not significant influence the dividend policy , ( 3 ) capital structure do not affect significant influence the value of the company , ( 4 ) profitability significant influence the value of the company , ( 5 ) its dividend policy has not been affecting the value of the company, ( 6 ) its dividend policy can mediate the influence of capital structure to value of the company, ( 7 ) its dividend policy can mediate influence of profitability to value of the company..